Social accountability and service delivery: Experimental evidence from Uganda - Nathan Fiala; Patrick Premand (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Corruption and mismanagement of public resources can affect the quality of government services and undermine growth. Can citizens in poor communities be empowered to demand better-quality public investments? We look at whether providing social accountability training and information on project performance can lead to improvements in local development projects. The program we study is unique in its size and integration in a national program. We find that offering communities a combination of training and information on project quality leads to significant improvements in household welfare. However, providing either social accountability training or project quality information by itself has no welfare effect. These results are concentrated in areas that are reported by local officials as more corrupt or mismanaged, suggesting local agents have significant information about where corruption and mismanagement is worse. We show evidence that the impacts come in part from community members increasing their monitoring of local projects, making more complaints to local and central officials and increasing cooperation. We also find modest improvements in people's trust in the central government. The results suggest that government-led, large-scale social accountability programs can strengthen communities' ability to address corruption and mismanagement as well as improve services.
Keywords: D7; H4; O1; 330; social accountability; community training; scorecards; corruption; service delivery